2020
DOI: 10.7705/biomedica.4644
|View full text |Cite
|
Sign up to set email alerts
|

Actividad antimicrobiana de hongos endófitos de las plantas medicinales Mammea americana (Calophyllaceae) y Moringa oleifera (Moringaceae)

Abstract: Introducción. Las enfermedades infecciosas son una causa importante de muertes en el mundo. La resistencia antimicrobiana es un problema global, por lo que es conveniente la investigación de nuevas fuentes de agentes antimicrobianos de origen natural potencialmente efectivos.Objetivo. Evaluar la actividad antimicrobiana de hongos endófitos de Mammea americana y Moringa oleifera en la cepa sensible (ATCC 29213) y en la cepa resistente (USb003) de Staphylococcus aureus, así como en la cepa sensible (ATCC 25922) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
6
0
2
Order By: Relevance
“…and Alternaria sp. The study by Mosquera et al ( 2020 ) also describes the isolation of fungal species, Cladosporium sp. and Penicillium sp.…”
Section: Endophytesmentioning
confidence: 99%
“…and Alternaria sp. The study by Mosquera et al ( 2020 ) also describes the isolation of fungal species, Cladosporium sp. and Penicillium sp.…”
Section: Endophytesmentioning
confidence: 99%
“…Quero externar meus sinceros agradecimentos aos autores dos trabalhos científicos e à Editora Artemis, pela organização desta obra. Mosquera, Criado & Guerra (2019). Se encontró que las semillas de Moringa poseen actividades biológicas como antipirética, antituberculosa, antitumoral, hepatoprotector, controla enfermedades del sistema genitourinario, entre otras.…”
Section: Apresentaçãounclassified
“…Acorde a estos resultados se concluye que la semilla y el aceite de Moringa poseen alto valor nutricional, alimenticio y farmacológico que beneficia la salud humana, por lo que se recomienda su aprovechamiento en las industrias antes mencionadas. Mosquera, Criado & Guerra (2019). Moringa seeds were found to possess biological activities such as antipyretic, antituberculous, antitumor, hepatoprotective, controls diseases of the genitourinary system, among others.…”
Section: Apresentaçãounclassified
“…Studies have shown the potential of Mammea americana bark to treat gastrointestinal disorders, including gastric ulcers in ethanolic, methanolic, and dichloromethane extracts [ 18 ]. Antimicrobial activity performed on crude ethanolic extract of endophytic fungi of M. americana showed that it has antimicrobial effects on S. aureus and E. coli [ 21 ]. Similarly, it has been reported that the ethanolic extract of the leaves and bark of this plant also possesses antibacterial activity against S. aureus [ 22 ], while its seeds were shown to have inhibitory activity for E. coli , Pseudomonas spp., and Salmonella ssp.…”
Section: Introductionmentioning
confidence: 99%